Evaluation of the Implementation and Impact of Performance-Based Budgeting (PBB) on Performance and Control Effectiveness in the Indonesian Public Sector - Azis, Aminudin (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
This study investigates the impact of Performance-Based Budgeting (PBB) implementation on financial control, managerial performance, and accountability in the public sector. A qualitative research method was used with a literature study approach to analyze relevant research reports. The results showed an evaluation of the implementation and impact of Performance-Based Budgeting (PBB) on performance and control effectiveness in the Indonesian public sector showed that PBB has great potential to improve transparency, accountability, efficiency, and control effectiveness in public financial management. However, the success of PBB is also influenced by factors such as effective leadership, managerial skills, and human resource capacity and information technology. PBB implementation challenges, such as resistance to change and limited resources, need to be overcome to achieve optimal results. Thus, with training, improved technological infrastructure, and organizational support, PBB can improve the efficiency of public financial management and the achievement of organizational goals in the public sector.